Tuberculous meningitis in children is characterized by compartmentalized immune responses and neural excitotoxicity - Ursula K. Rohlwink (Nature Portfolio, 2019)
Tuberculosis meningitis (TBM) is a severe form of TB with limited treatment options. Here, the authors perform RNA sequencing on whole blood and on ventricular and lumbar cerebrospinal fluid (CSF) samples from pediatric patients treated for TBM to characterize the immune response and tissue damage.